Pão sobre a mesa: um estudo exegético de Ex 25,23-30; 37,10-16; Lv 24,5-9 - Brey, Petterson (2023)
This doctoral thesis, through the methodological rigor of narrative analysis, proposes to carry out an exegetical study of Ex 25,23-30; 37.10-16; Lv 24.5-9. Such undertaking, therefore, requires reading the texts of instruction and execution of the construction of the table, as well as the prescription of the ritual of bread on the table, in a synchronous perspective. Furthermore, in view of the literary-theological sophistication of the Pentateuchal narratives, it is necessary to establish, with this analysis, the constituent values of the covenant between the LORD and his people on Sinai. Because, as a narrative locus of the scenes that shelter the object of study delimited for this thesis, the plot of the Sinaitic narratives, in turn, constitutes the heart of the Pentateuch. Thus, such textual portions catalyze the deeper meanings of the layers of meaning underlying the Torah narratives, with a view to forming the ritual wisdom that constituted the religion of Ancient Israel. It is understood, therefore, that the ritual of bread on the table symbolizes the materialization of the theological values that constitute the character of the LORD, as the foundation of his covenant. These values, therefore, expressed in divine behavior in the face of injustice and oppression, acting to free the oppressed, correspond to the features of the LORD's holiness. While the bread symbolizes God's protection and sustenance of the fleeing people, it, too, represents the core values of the elected kingdom of priests and holy nation, as representatives of the justice of the God of Israel. Moreover, under the understanding that hunger corresponds to the maximum degree of disfiguration of the image of God in men, caused by injustice and oppression perpetrated by the logics of power that exploit the domain of the sources of wealth and production of food on earth, the behavior that is required of those who have a table fellowship with the LORD, it is the action to guarantee decent access to food for all people. For whoever eats this bread feeds on the holiness of God and contracts covenant with him. Whoever is sanctified by the presence of the LORD shares bread